Initial experience with the glidesheath slender for transradial coronary angiography and intervention: A feasibility study with prospective radial ultrasound follow‐up. Issue 3 (6th November 2013) - Aminian, Adel; Dolatabadi, Dariouch; Lefebvre, Pascal; Zimmerman, Robert; Brunner, Philippe; Michalakis, Georges; Lalmand, Jacques
<x xml:space="preserve">Abstract</x> Objective The aim of this study is to evaluate the feasibility and safety of the Glidesheath Slender in routine transradial (TR) coronary angiography and intervention. Background In recent years, The TR approach has gained in popularity because of several advantages such as reduced vascular access site complications and immediate patient mobilization. Procedural success has been further improved through technological innovations and the development of less invasive devices. The Glidesheath Slender (Terumo, Tokyo, Japan) is a new dedicated radial sheath with a thinner wall and hydrophilic coating. It combines an inner diameter compatible with 6Fr guiding catheter with an outer diameter close to current 5Fr sheaths. Its use has the potential to decrease invasiveness and access site complications during TR procedures. Methods A total of 114 consecutive patients undergoing TR coronary angiography and/or PCI using the Gidesheath Slender were included in a prospective single‐center feasibility and safety study. Results Procedural success was 99.1% with only one case requiring conversion to femoral access. There were six minor hematomas but none of the patients experienced major vascular complications. The rate of symptomatic radial spasm was 4.4%. No case of major sheath kinking was noted. Doppler ultrasound examination of the radial artery at 1 month follow‐up was available in 113/114 patients with only one case of radial artery occlusion (RAO) (0.88%). Conclusions Routine use of the Glidesheath Slender for TR coronary angiography and interventions is safe and feasible with a high rate of procedural success and a low rate of RAO. © 2013 Wiley Periodicals, Inc.